PENGARUH PELAYANAN DAN KUALITAS JASA TERHADAP KEPUASAN PELANGGAN PADA PERUSAHAAN JASA PLN - Ricky Novayanto, 05.05.51.0026; liana, Lie (Students Journal of Economic and Management, 2012)
This research is a study that evaluated the effects of service and quality of service to customer satisfaction in service firms with services marketing theory perspective. In this study, researchers used a convenience sampling and sample size to obtain a sample of 100 respondents. Data obtained from respondents by distributing questionnaires containing questions about the service, service quality and customer satisfaction. Respondents were then in the testing data validity and reliability. The results showed all the variables valid and reliable. Further analysis using multiple linear regression to describe the relationship between the variables. The result is service and service quality significant positive effect on customer satisfaction. Thus, the higher the service will increase customer satisfaction and higher quality of service to enhance customer satisfaction. This study has limitations that the data sample is 100 respondents and do not consider other variables that could affect customer satisfaction. For further research, in order to expand the research by taking more samples and adding other variables are more than enough to represent the research. Keywords: Service, Service Quality and Customer Satisfaction.